P20 The association between asthma, corticosteroids and allostatic load biomarkers: a cross-sectional study. (12th November 2019) - Barry, L; O'Neill, C; Heaney, L
Abstract : Introduction and objectives: Allostatic load, a measure of 'wear and 'tear' from adapting to environmental challenges, has been suggested as a framework with which to understand the stress-related disruption on multiple systems of asthma. We aim to estimate for the first time the relationship between allostatic load (AL) and its constituent biomarkers, asthma and corticosteroid (CS) use among a large sample of the UK adult population while controlling for socioeconomic status. Methods: Data from Understanding Society (a nationally representative survey of UK community-dwelling adults) waves 1–3 (2009–2012) allowed the identification of a sex-specific risk profile across 12 biomarkers used to construct an AL index for a sample of 9, 816 individuals aged 16 years and over. Information on asthma status and medication prescribing was used to create groups broadly consistent with other UK based research using GINA guidelines: 1) No asthma diagnosis and no prescription for any CS (control group); 2) Physician diagnosed asthma and in receipt of respiratory medication (henceforth Currently Treated (CT) asthma) but no Inhaled CS (ICS) and no systemic CS (SCS) prescription; 3) CT asthma, ICS prescription but no SCS prescription; 4) CT asthma and SCS prescription. Regression analyses were used to examine the association of these CT asthma/CS prescribing groups with allostatic load and its constituent biomarkers while controlling for socioeconomic status. Results: Those with CT asthma and no corticosteroid prescription have an allostatic load 1.2 (p<0.001) higher than those without asthma and no corticosteroid prescription (control group). Those in receipt of systemic corticosteroids had the highest allostatic load approximately 1.4 times higher than the control group (p<0.001). This association with allostatic load was largely unchanged in sensitivity analyses and was likely driven by an association with specific biomarkers (dehydroepiandrosterone-sulfate and C-reactive protein, see figure 1). Conclusion: In relation to allostatic load, early ageing was present even in the mildest asthma group without prescriptions for corticosteroids: approximately equivalent to a penalty of 8 years on one's chronological age. Allostatic load is helpful in understanding the increased all-cause mortality and multi-morbidity observed in asthma.